Small ruminant production techniques - Ibrahim, H. (International Livestock Research Institute, 1998)
This training manual emphasises an integrated approach to research on small ruminants. Eleven modules cover the topics in an integrated approach to improving small ruminant productivity in sub-Saharan Africa. It starts with describing small ruminants in various agro-ecological zones in sub-Saharan Africa with emphasis on the prevailing production systems. The user is then introduced to the concepts and methodologies of farming systems research to better understand the needs of the smallholder farmer. The core of the manual presents knowledge and skills in the disciplines of reproduction, diseases, genetics, biometry, economics and communication. The manual ends by stressing the importance of transferring research results to farmers and the role of researchers in this vital process. This material includes audio-tutorial modules, slide series and posters.